Comparison and analysis of phylogenetic relationship based on internal transcribed spacer 1, its-1 fragment of eimeria tenella and eimeria acervulina from broiler chicken in korea - Myung-Jo You (Eurasian Journal of Veterinary Sciences)
Aim: The objective of the present study is the simple PCR assay that permits the detection of the Eimeria tenella, Eimeria acervulina that infect domestic fowl in Korea and making phylogenetic relation with in the same and neighboring species. Materials and Methods: The internal transcribed spacer 1 (ITS-1) region of ribosomal RNA genes of two poultry Eimeria species; E. tenella and E. acervulina were sequenced and analyzed the phylogenetic relationship among them from field isolates. Results: About the 273-bp and 147-bp sequence of ITS-1 of E. tenella and E. acervulina in Korea were similar reflected in the phylogram constructed using the partial nucleotide sequences. In case of E. tenella for homology searching the sequences among the same species was 98% and with E. necatrix was 89%. In case of E. acervulina sequence similarity within the same species was 97%, whereas the similarity E. maxima and E. mitis were 77% and 76%, respectively. ITS- 1 region of each Eimeria species had sufficient inter-specific sequence variation and the primer is sufficient to amplify each target Korean isolates. Conclusions: The molecular method examine in the present study appears useful for discriminating among similar Eimeria species providing useful methods for diagnosis and epidemiology of avian coccidial infection.